PROGRAM OPTIMALISASI PEMBELAJARAN MATEMATIKA DARI RUMAH DENGAN MEREFLEKSIKAN SEMANGAT BELAJAR SISWA PADA MASA PANDEMI COVID-19 - Ismawati Ismawati; Arditya Prayogi (As-Sidanah, 2022)
As a basic science from various fields, Mathematics is important to learn because it is also the basis for the development of science and technology. The existence of educational developments requires students to adapt to changes. The COVID-19 outbreak requires the learning process to be carried out online (in a network). However, in learning, optimization of learning must still be done which in this case must create a spirit of student learning by providing meaningful learning. This empowerment program is based on the limited conditions during the Pandemic which was carried out by providing tutoring, especially in mathematics. This learning mentoring program is carried out in a targeted manner through online and offline learning methods for SMP - MTs and SD - MI students in Karanganyar Village, Pekalongan Regency with a total of 67 students participating in the mentoring. The final result of this program is an overview of the differences between online and offline math tutoring. Optimization of mathematics learning is more visible in offline learning. This can be seen from the enthusiasm and motivation given to make students able to follow the lesson well so that the material is easy to understand. However, the end result of this program is that students are able to optimize learning, understand, and master mathematics better.